Explore BrainMass

Explore BrainMass

    Going from First to Second Derivative

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    I have a first derivative and a second derivative, how do you get from the first to the second, I can't solve it.

    Please see the attached file for the fully formatted problems.

    M'(t) = pe^t/(1 - t^tq)^2
    M''(t) = pe^t(1 + qe^t)/(1 - (e^t)q)^3

    © BrainMass Inc. brainmass.com November 24, 2022, 11:41 am ad1c9bdddf


    Solution Preview

    M'(t) = p*exp(t)/[1 - q*exp(t)]^2 = p*f1/f2
    M''(t) = p*(f2*f1' - f1*f2')/f2^2
    f1 = expt(t) => f1' = ...

    Solution Summary

    The method of going from a first to a second derivative is shown.